Suction Versus Nonsuction Drainage After Uniportal Video-Assisted Thoracoscopic Surgery: A Propensity Score-Matched Study - Zhou, Jian; Li, Chuan; Zheng, Quan; Guo, Chenglin; Lyu, Mengyuan; Pu, Qiang; Liao, Hu; Liu, Lunxu (Frontiers in Oncology, 2021)
Background. Uniportal video-assisted thoracoscopic surgery (UniVATS) was utilized with a rapid growth. The evidence is sparse, however, on whether to add external suction to water-seal drainage for chest drainage after UniVATS. This retrospective propensity score-matched study aimed to identify the necessity of adding external suction to chest drainage after UniVATS. Methods. Patients with lung cancer who underwent UniVATS were included from our prospectively maintained database. Patients were divided into 2 cohorts based on the addition of external suction to postoperative water-seal drainage or not. Propensity score-match analysis was performed to identify the impact of suction on chest tube duration, incidence of persistent air leak, hospital stay, and hospitalization cost. Multivariable model with interaction terms was constructed to identify impact of covariables on effect of suction. Results. The 2 cohorts matched well on baseline characteristics (non-suction: 173; suction: 96). Compared with non-suction group, suction group showed longer median chest tube duration (3 vs. 2 days, P=0.003), higher incidences of persistent air leak (9.4% vs. 1.2%, P=0.003) and persistent drainage (16.8% vs. 5.8%, P=0.007), and reduced drainage volume within first 3 postoperative days (386.90 vs. 504.78 ml, P=0.011). Resection extent was identified to mediate the relationship between suction and chest tube drainage. Conclusions. These findings discouraged adding external suction to water-seal drainage after UniVATS regarding longer chest tube duration and more persistent air leak. Patients undergoing lobectomy would benefit more from water-seal drainage without external suction compared with those doing sublobectomy.